Antifungal activity of the dill (Anethum graveolens L.) seed essential oil against strawberry anthracnose under in vitro and in vivo conditions. (13th December 2016) - Karimi, Kaivan; Arzanlou, Mahdi; Pertot, Ilaria
Abstract: Strawberry anthracnose, caused by Colletotrichum nymphaeae, is mainly controlled by the application of synthetic chemical fungicides. The present study assessed the antimicrobial activity of essential oils (EOs) from dill ( Anethum graveolens L.) seed against C. nymphaeae. The antifungal effects of dill seed EO on C. nymphaeae was initially evaluated in vitro and further extended as in vivo condition. The results indicate that in the contact and volatile assays, dill seed EO significantly inhibited mycelial growth of C. nymphaeae at all concentrations tested. Conidia germination was also significantly inhibited at concentrations of 250 – 1000 ppm. Disease incidence and severity of anthracnose on strawberry fruits were significantly reduced compared with infected control, from concentrations of 500 and 50 ppm, respectively. The results confirm the efficacy of dill seed EO against C. nymphaeae, which may represent an alternative to synthetic chemical fungicides to control strawberry anthracnose pre- and post-harvest.